Crystallographic anisotropy of nonequilibrium solute capture. (1st October 2020) - Yu, Xiao-Xiang; Perepezko, John H.; Marks, Laurence D.
Abstract: We demonstrate large, crystallographic anisotropy in nonequilibrium solute capture. Under identical conditions, differently oriented grains of a Ni-30Cr (wt.%) alloy were oxidized at 600°C for 60 s. For a Ni(Cr) (100) oriented grain, a solute captured rock salt oxide formed with a cube-cube epitaxial orientation. In contrast, for a Ni(Cr) (111) oriented grain, a solute captured corundum oxide formed with the (0001) basal plane parallel to (111). There are clear indications from the morphologies that are present – islands growing outwards for rock salt and islands growing inwards for corundum – that the oxide growth is dominated by kinetics, not thermodynamic factors. Since the interfacial conditions for nonequilibrium solute capture differ for cases where the metal/oxide boundary is moving (the (111) case) and where it is not (the (100) case), these results indicate that crystallographic anisotropy will have substantial effects which cannot be ignored in oxidation or corrosion. Graphical Abstract: Image, graphical abstract